Re-conceptualising the relationship between de-familialisation and familialisation and the implications for gender equality – the case of long-term care policies for older people. Issue 4 (31st October 2018) - Eggers, Thurid; Grages, Christopher; Pfau-Effinger, Birgit; Och, Ralf
Abstract: This article explores how far the concepts of de-familialisation/familialisation are adequate to the classification of long-term care (LTC) policies for older people. In the theoretical debate over LTC policies, de-familialising and familialising policies are often treated as opposites. We propose re-conceptualising the relation between de-familialisation and familialisation, arguing that they represent substantially different types of policy that, in theory, can vary relatively autonomously. In order to evaluate this theoretical assumption, this article investigates the relation between the generosity level of LTC policies on extra-familial care, and the generosity level of LTC policies on paid family care, introducing a new multi-dimensional approach to measuring the generosity of LTC policy for older persons. It also explores the consequences of this for gender equality. The empirical study is based on a cross-national comparison of LTC policies in five European welfare states which show significant differences in their welfare state tradition. Data used are from document analysis of care policy law, the Mutual Information System on Social Protection, the European Quality of Life Survey and the Organisation for Economic Co-operation and Development. The findings support the argument that de-familialising and familialising LTC policies can vary relatively independently of each other in theory. It turns out that we get a better understanding of the relationship between LTC policy and gender equality if we analyse the role of different combinations of extra-familial and familial LTC policies for gender equality. The paper brings new insights into the ways welfare states act in regard to their LTC policies. It helps to clarify how the concept of de-familialisation/familialisation can be understood, and what this means for the relationship between LTC policies and gender equality.